2007
DOI: 10.1002/ejsp.393
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and explicit attitudes respond differently to increasing amounts of counterattitudinal information

Abstract: This research examined the processes by which explicit and implicit attitudes changed to systematically differing levels of counterattitudinal (CA) information. Explicit attitudes changed quickly in response to relatively small amounts of CA information, reflecting rule-based reasoning. On the other hand, implicit attitudes changed more slowly in the face of CA information, reflecting the progressive accretion of evaluation-attitude object pairings. Thus, explicit attitudes were extremely malleable and changed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
122
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(142 citation statements)
references
References 29 publications
11
122
6
Order By: Relevance
“…Importantly, however, the AA effect on implicit evaluations remained significant after controlling suggesting that, once established, implicit evaluations cannot be easily changed (Gregg et al, 2006;Rydell, McConnell, Strain, Claypool, & Hugenberg, 2007). Recently, however, research has shown that new valenced information about a stimulus can lead to a rapid revision of implicit evaluations, but only when this information is considered highly diagnostic about the evaluative properties of this stimulus (Mann, Cone & Ferguson, 2015; …”
Section: Approach-avoidance Instruction 13mentioning
confidence: 99%
“…Importantly, however, the AA effect on implicit evaluations remained significant after controlling suggesting that, once established, implicit evaluations cannot be easily changed (Gregg et al, 2006;Rydell, McConnell, Strain, Claypool, & Hugenberg, 2007). Recently, however, research has shown that new valenced information about a stimulus can lead to a rapid revision of implicit evaluations, but only when this information is considered highly diagnostic about the evaluative properties of this stimulus (Mann, Cone & Ferguson, 2015; …”
Section: Approach-avoidance Instruction 13mentioning
confidence: 99%
“…As implicit and explicit attitudes are influenced by different processes (Gawronski & Strack, 2004, Olson & Fazio, 2006, asymmetric attitude changes may occur, which in turn can lead to discrepancies between implicit and explicit attitudes (Gawronski & Bodenhausen, 2006;Rydell, McConnell, Strain, Claypool, & Hugenberg, 2006). It can therefore be expected that this might be true for implicit and explicit self-esteem, too.…”
mentioning
confidence: 99%
“…We varied between participants the number of positive and negative behaviours attributed to each man. Theory and empirical evidence suggest that just like deliberate evaluation, automatic evaluation has a straightforward reaction to such information: more positive behaviours cause more automatic liking (Bar-Anan & Nosek, 2012;Ratliff & Nosek, 2010;Rydell et al, 2007;Nosek, 2005;Smith et al, 2013). That manipulation is expected to cause clear effects on automatic evaluation regardless of the measure.…”
Section: Overview Of Experimentsmentioning
confidence: 99%
“…Research on impression formation (Ratliff & Nosek, 2010;Rydell, McConnell, Strain, Claypool, & Hugenberg, 2007), persuasion (Horcajo, Briñol, & Petty, 2010;Smith, De Houwer, & Nosek, 2013), and other forms of evaluative learning (Olson & Fazio, 2001;Stahl & Unkelbach, 2009) often uses novel objects as stimuli and indirect measures as the dependent variable. Previous comparative studies of indirect measures addressed concepts that participants have known for days, weeks, and years.…”
mentioning
confidence: 99%